HUBUNGAN SELF-RATED ORAL HEALTH TERHADAP INDEKS KUNJUNGAN RUTIN PEMERIKSAAN KESEHATAN GIGI DAN MULUT KE DOKTER GIGI - Dyah Nawang Palupi Pratamawari; Ahmad Marwan Hadid (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Self-Rated Oral Health (SROH) is a simple measurement of the general condition of oral health based on self-assessment. SROH is an important key that has an impact on welfare and quality of life. This study aims to determine the relationship between SROH and the routine dental visit every six months.Method: Using a cross-sectional data collected from the population of the FKG UB students, there are 97 students that have been surveyed as respondents. This research was taken with questionnaire of SROH and information about doing dental checkup was obtained.Results: Self-Rated Oral Health (SROH) of the student on average is sufficient (51.6%). FKG UB students who routinely do a dental visit are 30.9%. Respondents with good Self-Rated Oral Health have a higher percentage for a routine dental checkup (RDCU). Based on the Pearson Correlation Test, the study found that the SROH and RDCU relationship has a significant relationship (p> 0.05).Conclusion: There is a significant relationship between Self-Rated Oral Healthstudents with a dental visit every six months